Experimental and Theoretical Study on Sm/Eu-Gd Extraction by P204 and [A336][P204] - N. A., Ismail; M. A., Abdul Aziz; A., Hisyam (IOP Publishing, 2020)
Extraction of rare earth using ionic liquid as extractant become an alternative practice to replace the common volatile organic solvents in recent years. In general, the work to extract rare earth element, require a large number of extraction stage, and different extractant used resulted in different number of extraction needed. Therefore an analysis on the theoretical number of stages is necessary prior to laboratory work. This study was designed to compare between the number of extraction stages required by 2- ethylhexyl phosphoric acid mono 2-the ester (P204), a common rare earth extractant with a bifunctional ionic liquid, and [A336][P204] in a counter-current extraction process for the separation of Sm in Sm-Eu-Gd mixed solution. The value of the separation factor (β) of both extractants, was obtained from the experimental work, while other process parameters were calculated using the counter-current theory developed by Xu Guangxian. Extraction of Sm using [A336][P204] was optimum in 3.0 M of nitric acid, with organic to aqueous (O/A) ratio of 4:1, while the optimum condition for P204 was when the medium was 2.0 M of hydrochloric acid and 7:3 of O/A ratio. The β value for the optimized condition for P204 was lower compared to the condition for [A336][P204] at β:1.93 and β:2.81, respectively. To derive an optimum extraction condition to calculate the number of extraction stage, target purity and recovery ratio were set to 99.9% and 90%, respectively, for both extractants. As a result, [A336][P204] was able to reduce the number of extraction stage by 5 compared to P204. The result indicated that [A336][P204] is preferable over P204 from the viewpoint of economic efficiency.